Methodological strategies implemented to improve speaking skills of the eleventh grade students at Lic .Lucinda Rosa Videa Institute in Pueblo Nuevo during the II semester 2014 - Benavides Videa, Jakeline del Rosario | Centeno Martínez, Yoseling Jassiell | Pérez Acevedo, Norlan Ruddy | Mairena, Eudomilia Urrutia Mairena Eudomilia Urrutia (UNAN-Managua, FAREM-Estelí, Nicaragua, 2014)
Oral communication is an important part of everyday activities. It allows expressing ideas, and feelings, exchange information, and learn about other cultures, but speaking English confidently is a problem that students present in our high school. Students are afraid of speaking in class, they are afraid of pronouncing the wrong words and expressing themselves correctly in English. In some cases students have the answer to the activities given by the teacher, but they do not like to participate. Teachers have to apply methodological strategies to allow students overcome their difficulties and besides foster communicative activities that are confidence, fluency and sharing accurate opinions and ideas among students and other people.